Chapter 4 Localizing Aboriginal and Pacific performance on internationalized stages 1967- 73 - Harris, Amanda (Taylor & Francis, 2021)
In 1967 Aboriginal and Torres Strait Islander people successfully campaigned for a referendum for constitutional change, releasing them from policies restricting movement outside of their home states and territories of residence. This chapter interrogates the contested space for representation of Aboriginal performance in the years following the referendum. New companies for Aboriginal music and dance performance flourished after 1967 and began to tour outside Australia, including to Japan, Fiji, and the USA. Non-Indigenous performers such as Beth Dean and Victor Carell, previously representing Aboriginal culture in their shows, quickly had to revise their approaches and soon began co-ordinating international music and dance performances by the owners of the traditions, instead of performing them. New companies included the Aboriginal Theatre Foundation (formed in 1969) and the South Pacific Festival of Arts (formed in 1972, building on the 1970 Ballet of the South Pacific). Some of the key musicians/dancers in these new performances, David Gulpilil, David Blanasi, and Djoli Laiwanga, went on to prominent careers as recording artists, touring musicians, and, in Gulpilil's case, in film. The chapter considers how these new contexts for cultural exchange were internationalized while resisting globalization, emphasizing localized performances by the owners of the songs and dances themselves.